Synthesis of diluted magnetic semiconductor ZnS:Cr and ZnS:(Cr+V) nanoparticles for spintronic applications. (July 2023) - Poornaprakash, B.; Puneetha, Peddathimula; Subramanyam, K.; Kwon, Min-Woo; Lee, Dong-Yeon; Siva Pratap Reddy, M.; Sangaraju, Sambasivam; Al-Asbahi, Bandar Ali; Kim, Y.L.
Abstract: The design of optimally diluted magnetic semiconductors that exhibit strong ferromagnetism at room temperature is also imperative for developing spintronic devices. In this study, we describe the wet chemical preparation and characterization of ZnS, ZnS:Cr (1 at%), ZnS:Cr (1 at%) + V (1 at%), and ZnS:Cr (1 at%) + V (2 at%) NPs for spin-electronic device applications. Wide-ranging structural analyses suggested the incorporation of both Cr and V ions into the ZnS system. Morphological analysis revealed that the synthesized samples were in the nanoregime with a zero-dimensional alignment. Photoluminescence (PL) spectra displayed diminished luminescence intensity with doing and co-doping. and Electron paramagnetic resonance analysis revealed the presence and augmentation of spins with increasing V co-dopant concentration in the ZnS:Cr (1 at%) host lattice. Vibrating sample magnetometer analysis revealed that the ZnS:Cr (1 at%), ZnS:Cr (1 at%) + V (1 at%), and ZnS:Cr (1 at%) + V (2 at%) NPs exhibited strong ferromagnetism with clear hysteresis loops at room temperature.